Comparative Advantage in the 24/7 Economy: Time-Zone Differences and Service Trade Flows - Arundhati Sinha Roy; Anwesha Aditya; Siddhartha Chattopadhyay; Sugata Marjit (CESifo GmbH, 2024)
Traditional gravity models posit an inverse relationship between geographical distance and bilateral trade due to increased transportation costs. However, recent literature suggests that bilateral service trade may increase between two countries located at an appropriate geographical distance. Using the Poisson Pseudo-Maximum Likelihood (PPML) method, this research analyses two key effects of time difference for 162 countries in 2018 - the continuity effect (enabling 24/7 operations) and the synchronization effect (influenced by cultural and/or institutional differences) for aggregate services, ICT-enabled services, and travel-transportation services. Our findings indicate a positive continuity effect across all service categories, while the synchronization effect varies across categories. We also find that 8-10 hour time difference between two countries appears most advantageous for ICT-enabled service trade between them. This paper underscores the importance of ICT and physical infrastructure, coupled with transparent governance, to boost service trade.
Keywords: F10; F14; L86; 330; service trade; time zone difference; continuity effect; synchronization effect; information and communication technology (ICT)